Having Fun (and Commercial Success) with Josiphos and Related Chiral Ferrocene Based Ligands. Issue 1 (3rd December 2020) - Blaser, Hans Ulrich; Pugin, Benoît; Spindler, Felix
Abstract: The Josiphos ligand family is arguably one of the most versatile classes of chiral ligands with a wide range of applications, including one of the two largest known enantioselective catalytic hydrogenations. In this personal account, we take a look back at the beginning and describe the role Antonio Togni has played to reach this point and the significance of his contributions for the commercial success, especially concerning today's ligand business of Solvias . This seems a fitting point in time in light of Antonio 's statement on his ETH home page that he 'is working as a professor at this institution since 1992 (a few more months to go), not looking for a job' and that the three authors have already retired for some time ( H. U. B .) or are about to retire soon ( B. P ., F. S .). Abstract :